2020
DOI: 10.21203/rs.3.rs-49014/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“I have SMA, SMA doesn’t have me”- A Qualitative Snapshot Into the Challenges, Successes, and Quality of Life of Sma Adolescents and Young Adults

Abstract: Background: With the approval of two treatments for spinal muscular atrophy (SMA) and several promising therapies on the horizon, the SMA adolescent and young adult populations are expected to evolve in the coming years. It is imperative to understand this cohort as it exists today to provide optimal care and resources, as well as to assess possible treatment effects over time. In 2018, Cure SMA launched two initiatives geared towards understanding adolescents and young adults with SMA, ages 12-25. First, Cure… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The findings of this survey supplement are discussed in a separate publication. 11 Based on an expected response rate of about 20%, the authors anticipated approximately 80 responses that would elicit a 95% confidence level and a 9.8% margin of error.…”
Section: Study Proceduresmentioning
confidence: 99%
“…The findings of this survey supplement are discussed in a separate publication. 11 Based on an expected response rate of about 20%, the authors anticipated approximately 80 responses that would elicit a 95% confidence level and a 9.8% margin of error.…”
Section: Study Proceduresmentioning
confidence: 99%
“…32,52 Some patients with SMA are concerned that portraying SMA as a disease to be "eradicated" with novel drugs may engender negative views toward SMA and disability, or that drug development may come at a cost for everyday interventions (such as vans or wheelchairs) that significantly impact adult patients. 52 While adults with late-onset SMA do struggle with physical impairments and access to a diverse array of healthcare needs, many patients lead meaningful and productive lives 53,54 and the benefits of prenatal gene therapy may not appear to outweigh the risks. Ultimately, patients' decisionmaking regarding prenatal therapy will be affected by the same factors regarding postnatal treatment, such as cost, risk factors, available information, side effects, insurance coverage, time constraints, access to clinical sites, functional status, and disability identity.…”
Section: Attitudes Toward Fetal Trials and Therapiesmentioning
confidence: 99%
“…A series of 25 interviews conducted with SMA adults in Australia highlighted the challenges in mental health that need to be met [18]. Mazzella et al found that SMA patients reported their mental health, including anxiety and depression, to be significantly affected by disease [19].…”
Section: Introductionmentioning
confidence: 99%